Transition metal complexes of bulky, electron-rich N-phosphanyl-substituted N-heterocyclic carbenes (NHCP ligands): small bite angle four-membered (κ-C,κ-P) chelate structures - Nägele, Philipp; Herrlich, Ulrike; Rominger, Frank; Hofmann, Peter (Organometallics, 2013)
Bulky, electron-rich N-phosphanyl-substituted N-heterocyclic carbenes (NHCP ligands: EtCNP 3, MesCNP 5a, DippCNP 5b) are potential ligands for strained, very small bite angle four-membered transition metal chelate complexes with (κ-C,κ-P) metal coordination. Various compounds of this type have been synthesized and were fully characterized inter alia by X-ray crystallography. Reactions of isolated NHCP species 3, 5a, and 5b with appropriate metal precursors furnished a series of (κ-C,κ-P)-coordinated four-membered NHCP chelate complexes for the metals of the nickel triad and for ruthenium. The cis-dimethyl Pd(II) complex (MesCNP-κC,κ-P)PdMe2 (8) reacted at room temperature with acceptor-substituted alkenes such as fumaronitrile and maleic anhydride to yield the corresponding η2-olefin complexes 9 and 10 with reductive elimination of ethane. Palladacyclopentadiene complex 11 was formed by addition of two equivalents of dimethyl acetylene dicarboxylate to complex 8 via alkyne-alkyne coupling.